Aspectos da regulação sobre o ensino a distância no Brasil - Caram, Nirave Reigota; Bizelli, José Luís (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This article presents a reflection on the historical aspects and legislation on Distance Learning (DL). For this, a bibliographic and documentary research was performed with the goal of raising the necessary notes for discussion. The text begins with the characterization of the current society, the Information Society, which supports the modern distance education, which uses information and communication technologies (ICTs) to establish the process of learning teaching. Five stages of the EAD are identified. Later, the Brazilian legislation concerning the DL is punctuated, starting with the passage by Article 80 of the Guidelines and Bases Law -. LBD (Law 9394/96) along with the critical analysis of Decree 5,622 / 05. Finally, in the final considerations is discussed the negative image that the DL carries by the Brazilian population and obstacles in the existing rules that hinder the democratization of access to education that aims DL.